In defense of class struggle - Bedford, Laura (Critical criminology, 2022)
In his article, "In Defense of Resistance," Ferrell (2019) argues for the importance and centrality of the study of everyday and emergent acts of resistance to unjust power and authority. In my response, I contend that by failing to position contemporary resistance within a coherent theory of the production and reproduction of real life under capitalism, support for free-floating forms of resistance may serve to legitimize and strengthen the status quo, rather than challenge it. Through a Marxist lens, I call for a renewed criminological focus on: (1) the criminogenic nature of capitalism and its structures of exploitation of people and the environment; (2) class struggle and the possibility of a post-capitalist society based on an eco-socialist mode of production; and, (3) the possible consequences of not moving beyond capitalism in the twenty-first century.